The moderating effect of technology orientation on the relationship between product innovation, process innovation, organizational learning capability and SME’s performance - Tariq, Tamoor Ali; Mad Lazim, Halim; Iteng, Rosman (2019)
Small and medium enterprises (SMEs) are the backbone of economy therefore play a critical role for socioeconomic development of a country. Prior studies have discussed several factors to explain how SMEs performance can be improved such as product innovation (PDI), process innovation (PCI), organizational learning capability (OLC). However, literature indicated inconsistent relationship between PDI, PCI, OLC and SMEs performance. Thus, this study proposed technology orientation as a potential moderator to strengthen their existing relationship. Moreover, this unique framework is supported by two theories namely, resource-based view (RBV) and dynamic capability view (DVC). Hence, this study recommends empirical testing of the proposed conceptual model across various industries.